Travailler avec/contre le format - Éthique et esthétique dans l’œuvre avec figures de Stanley Spencer - Liliane Louvel (Interfaces)
For Stanley Spencer formatting was always linked to his own « inner vision » and inspiration. It reveals a kind of anachronistic taste for series, triptychs and long narrow formats allowing him to paint narrative sequences with figures. Deeply inspired by the Italian Primitive painters, Spencer decorated the famous Burghclere Chapel with frescoes evoking his war memories and hoped to renew this major feat with “The Church House Project”, but he never found a commissioner. Fortunately its several series display his creativity. The War commission sending him to Glasgow to paint Shipbuilding on the Clyde gave him once more the opportunity to produce several magnificent series. While having to cope with production constraints the painter often had to work with/against formats: adding to them, cutting them up, even adapting them to new projects. Thus these alterations testify to the necessity to working with reality, were it to entail painful sacrifices.